High-durability low-friction optical coating formula and preparation method thereof
Through the combination of modified polymethylsiloxane resin and nanomaterials, the durability and friction problems of optical coatings are solved, and the preparation of high-durance and low-friction optical coatings is achieved, which significantly improves the performance of the optical coatings.
Patent Information
- Application Number
- CN202411313863.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-03
AI Technical Summary
Existing optical coatings are prone to failure due to friction and scratching during use, resulting in poor durability and high friction coefficient, which affects the efficiency and contrast of the optical system.
Using modified polymethylsiloxane resin formula, the durability of the coating is improved by graphene quantum dot solution and carbon nanotube modification, and the addition of nanodiamond particles and titanium dioxide nanoparticles enhances scratch resistance and self-cleaning function. , reduce the friction coefficient.
It significantly improves the durability and UV resistance of the coating, reduces the friction coefficient, extends the aging rate of the coating, and improves the overall performance of the optical coating.
Smart Images

Figure BDA0005051547930000101
Abstract
Description
Technical Field
[0001] The present application relates to the field of optical coatings, and in particular to a high-durability, low-friction optical coating formulation and a preparation method thereof. Background Art
[0002] Optical coating is a kind of functional coating specially used on the surface of optical components.
[0003] Through special formula design, optical coatings can reduce the reflectivity of the surface of optical components, reduce light loss and reflection interference. This is crucial to improving the efficiency and contrast of optical systems. Since optical components may be subjected to external forces such as friction and scratches during use, causing the optical coating to fail, based on the above statements, this application provides a high-durability, low-friction optical coating formula and its preparation method. Summary of the invention
[0004] The purpose of this application is to improve the durability of high-durability, low-friction optical coatings and reduce the surface friction coefficient. Compared with the prior art, a high-durability, low-friction optical coating formula and a preparation method thereof are provided.
[0005] In a first aspect, the present application provides a high-durability, low-friction optical coating formulation, comprising the following raw materials in parts by weight: 60-95 parts of modified polymethylsiloxane resin, 15-25 parts of nano-boron nitride flakes, 10-25 parts of modified filler, 2-7 parts of fluorinated polyether, 1-5 parts of hyperbranched polysiloxane, 5-15 parts of bio-based solvent, and 1-3 parts of photoinitiator;
[0006] The modified polymethylsiloxane resin is prepared by the following method:
[0007] The polymethylsiloxane resin, graphene quantum dot solution, carbon nanotubes and toluene are weighed in a mass ratio of 20-30:2-3:2-3:70 for later use, the weighed polymethylsiloxane resin and toluene are evenly mixed to form a mixed solution with a concentration of 8%-25%, the weighed graphene quantum dot solution and carbon nanotubes are added to the mixed solution, and the mixture is stirred at room temperature for 4-7 hours at a stirring speed of 800-1000 r / min. After the mixture is formed, the toluene solvent is evaporated, and the mixture is homogenized by an ultrasonic oscillator to obtain a modified polymethylsiloxane resin.
[0008] Preferably, the modified filler comprises nano-diamond particles and titanium dioxide nano-particles in a mass ratio of 3:5-15.
[0009] Preferably, the modified filler is prepared by the following method:
[0010] a. Weigh nanodiamond particles having an average particle size of 8-25 nm and titanium dioxide nanoparticles according to a mass ratio and mix them to form a mixture A. Add ethanol to the mixture A and put it into an ultrasonic dispersion device for a dispersion time of 0.2-0.6 h to obtain a mixed suspension.
[0011] b. Slowly add the ionic liquid to the dispersed mixed suspension, stir and mix at a stirring speed of 200-300r / min, stir for 0.5-1h, and then react at a temperature of 30-70°C for 1-4h to obtain a mixed solution B;
[0012] c. Centrifuge the mixed solution B at a speed of 4000-8000 r / min for 0.1-0.3 h;
[0013] d. Wash the product after centrifugation of mixed solution B with deionized water and organic solvent alternately for 2-4 times, transfer it into a vacuum drying oven for vacuum drying, and obtain the desired modified filler.
[0014] By adopting the above scheme, the present application modifies the polymethylsiloxane resin through graphene quantum dot solution and carbon nanotubes, and utilizes the hardness and thermal stability of the carbon nanotubes and the high thermal conductivity and optical transparency of the graphene quantum dot solution to improve the durability of the polymethylsiloxane resin. At the same time, by adding modified nano-diamond particles and titanium dioxide nanoparticles, the scratch resistance of the coating can be significantly enhanced, the friction coefficient can be reduced, and the coating can be given a self-cleaning function, which helps to improve the durability and UV resistance of the coating, and further reduce the aging rate of the coating, thereby improving durability and reducing the friction coefficient.
[0015] Preferably, the mass ratio of the mixture A to ethanol is 1:30-60, the ionic liquid is 1-butyl-3-methylimidazolium tetrafluoroborate solution, and the ratio of the ionic liquid to the mixed solution B is 0.1-0.2:1.
[0016] Preferably, the vacuum drying temperature is 40-70° C., and the drying time is 5-12 hours.
[0017] Preferably, the bio-based solvent is butyl acetate, and the photoinitiator is benzoin ethyl ether.
[0018] In a second aspect, the present application provides a method for preparing a high-durability, low-friction optical coating, comprising the following preparation steps:
[0019] S1. Weigh the raw materials modified polymethylsiloxane resin, nano boron nitride flakes, modified filler, fluorinated polyether, hyperbranched polysiloxane, bio-based solvent, and photoinitiator by weight for later use;
[0020] S2, adding the nano boron nitride flakes and the modified filler into the modified polymethylsiloxane resin, and performing ultrasonic dispersion to make them uniformly dispersed in the solvent;
[0021] S3, adding fluorinated polyether, hyperbranched polysiloxane, and bio-based solvent in sequence and stirring evenly;
[0022] S4. Add photoinitiator and stir again to obtain the desired high-durability and low-friction optical coating.
[0023] Compared with the prior art, the advantages of the present application are as follows: the present application modifies polymethylsiloxane resin by using graphene quantum dot solution and carbon nanotubes, and utilizes the hardness and thermal stability of carbon nanotubes and the high thermal conductivity and optical transparency of graphene quantum dot solution to improve the durability of polymethylsiloxane resin; at the same time, by adding modified nano-diamond particles and titanium dioxide nano-particles, the scratch resistance of the coating can be significantly enhanced, the friction coefficient can be reduced, and the coating can be given a self-cleaning function, which helps to improve the durability and UV resistance of the coating, and further reduce the aging rate of the coating, thereby improving durability and reducing the friction coefficient. DETAILED DESCRIPTION
[0024] The present application is further described in detail below with reference to the embodiments.
[0025] Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without making any creative work shall fall within the scope of protection of this application.
[0026] Embodiment 1:
[0027] The present invention provides a high-durability, low-friction optical coating formula, comprising the following raw materials in parts by weight: 60 parts of modified polymethylsiloxane resin, 15 parts of nano boron nitride flakes, 10 parts of modified fillers, 2 parts of fluorinated polyether, 1 part of hyperbranched polysiloxane, 5 parts of bio-based solvents, and 1 part of photoinitiator;
[0028] Specifically, the bio-based solvent is butyl acetate, and the photoinitiator is benzoin ethyl ether.
[0029] The modified polymethylsiloxane resin is prepared by the following method:
[0030] Weigh polymethylsiloxane resin, graphene quantum dot solution, carbon nanotubes and toluene in a mass ratio of 20:2:2:70 for later use, mix the weighed polymethylsiloxane resin and toluene evenly to form a mixed solution with a concentration of 8%, add the weighed graphene quantum dot solution and carbon nanotubes to the mixed solution, stir and mix at room temperature for 4 hours at a stirring speed of 800 r / min, evaporate the toluene solvent after forming a mixture, and then use an ultrasonic oscillator to homogenize the mixture to obtain a modified polymethylsiloxane resin.
[0031] It should be noted that the modified filler includes nano-diamond particles and titanium dioxide nano-particles in a mass ratio of 3:5.
[0032] The modified filler is prepared by the following method:
[0033] a. Nano-diamond particles with an average particle size of 8 nm and titanium dioxide nanoparticles were weighed and mixed to form a mixture A according to a mass ratio, ethanol was added to the mixture A, and the mixture was put into an ultrasonic dispersion device for a dispersion time of 0.2 h to obtain a mixed suspension, wherein the mass ratio of the mixture A to the ethanol was 1:30;
[0034] b. Slowly add the ionic liquid to the dispersed mixed suspension, wherein the ionic liquid is 1-butyl-3-methylimidazolium tetrafluoroborate solution, the ratio of the ionic liquid to the mixed solution B is 0.1:1, stir and mix at a stirring speed of 200 r / min, stir for 0.5-1h, and then place at a temperature of 30°C for 1h to react to obtain a mixed solution B;
[0035] c. Centrifuge the mixed solution B at 4000 r / min for 0.1 h;
[0036] d. The product after centrifugation of the mixed solution B was washed alternately with deionized water and an organic solvent twice, and then transferred to a vacuum drying oven for vacuum drying at a temperature of 40°C and a drying time of 5 hours to obtain the desired modified filler.
[0037] A method for preparing a high-durability, low-friction optical coating comprises the following preparation steps:
[0038] S1. Weigh the raw materials modified polymethylsiloxane resin, nano boron nitride flakes, modified filler, fluorinated polyether, hyperbranched polysiloxane, bio-based solvent, and photoinitiator by weight for later use;
[0039] S2, adding the nano boron nitride flakes and the modified filler into the modified polymethylsiloxane resin, and performing ultrasonic dispersion to make them uniformly dispersed in the solvent;
[0040] S3, adding fluorinated polyether, hyperbranched polysiloxane, and bio-based solvent in sequence and stirring evenly;
[0041] S4. Add photoinitiator and stir again to obtain the desired high-durability and low-friction optical coating.
[0042] Embodiment 2:
[0043] The present invention provides a high-durability, low-friction optical coating formula, comprising the following raw materials in parts by weight: 95 parts of modified polymethylsiloxane resin, 25 parts of nano boron nitride flakes, 25 parts of modified filler, 7 parts of fluorine-containing polyether, 5 parts of hyperbranched polysiloxane, 15 parts of bio-based solvent, and 3 parts of photoinitiator;
[0044] Specifically, the bio-based solvent is butyl acetate, and the photoinitiator is benzoin ethyl ether.
[0045] The modified polymethylsiloxane resin is prepared by the following method:
[0046] Weigh polymethylsiloxane resin, graphene quantum dot solution, carbon nanotubes and toluene in a mass ratio of 30:3:3:70 for later use, mix the weighed polymethylsiloxane resin and toluene evenly to form a mixed solution with a concentration of 25%, add the weighed graphene quantum dot solution and carbon nanotubes to the mixed solution, stir and mix at room temperature for 7 hours at a stirring speed of 1000 r / min, evaporate the toluene solvent after forming a mixture, and then use an ultrasonic oscillator to homogenize the mixture to obtain a modified polymethylsiloxane resin.
[0047] It should be noted that the modified filler includes nano-diamond particles and titanium dioxide nano-particles in a mass ratio of 3:15.
[0048] Wherein, the modified filler is prepared by the following method:
[0049] a. Nano-diamond particles with an average particle size of 25 nm and titanium dioxide nanoparticles were weighed in a mass ratio and mixed to form a mixture A. Ethanol was added to the mixture A and put into an ultrasonic dispersion device for a dispersion time of 0.6 h to obtain a mixed suspension, wherein the mass ratio of the mixture A to the ethanol was 1:60;
[0050] b. Slowly add the ionic liquid to the dispersed mixed suspension, wherein the ionic liquid is 1-butyl-3-methylimidazolium tetrafluoroborate solution, the ratio of the ionic liquid to the mixed solution B is 0.2:1, stir and mix at a stirring speed of 300 r / min, stir for 1 hour, and then place at a temperature of 70°C for 4 hours to obtain a mixed solution B;
[0051] c. Centrifuge the mixed solution B at 8000 r / min for 0.3 h;
[0052] d. The product after centrifugation of the mixed solution B was washed alternately with deionized water and an organic solvent for 4 times, and then transferred to a vacuum drying oven for vacuum drying at a temperature of 70°C and a drying time of 12 h to obtain the desired modified filler.
[0053] A method for preparing a high-durability, low-friction optical coating comprises the following preparation steps:
[0054] S1. Weigh the raw materials modified polymethylsiloxane resin, nano boron nitride flakes, modified filler, fluorinated polyether, hyperbranched polysiloxane, bio-based solvent, and photoinitiator by weight for later use;
[0055] S2, adding the nano boron nitride flakes and the modified filler into the modified polymethylsiloxane resin, and performing ultrasonic dispersion to make them uniformly dispersed in the solvent;
[0056] S3, adding fluorinated polyether, hyperbranched polysiloxane, and bio-based solvent in sequence and stirring evenly;
[0057] S4. Add photoinitiator and stir again to obtain the desired high-durability and low-friction optical coating.
[0058] Embodiment 3:
[0059] The present invention provides a high-durability, low-friction optical coating formula, comprising the following raw materials in parts by weight: 70 parts of modified polymethylsiloxane resin, 20 parts of nano boron nitride flakes, 20 parts of modified filler, 5 parts of fluorine-containing polyether, 4 parts of hyperbranched polysiloxane, 10 parts of bio-based solvent, and 2 parts of photoinitiator;
[0060] Specifically, the bio-based solvent is butyl acetate, and the photoinitiator is benzoin ethyl ether.
[0061] The modified polymethylsiloxane resin is prepared by the following method:
[0062] Weigh polymethylsiloxane resin, graphene quantum dot solution, carbon nanotubes and toluene in a mass ratio of 15:2:3:70 for later use, mix the weighed polymethylsiloxane resin and toluene evenly to form a mixed solution with a concentration of 15%, add the weighed graphene quantum dot solution and carbon nanotubes to the mixed solution, stir and mix at room temperature for 6 hours at a stirring speed of 900 r / min, evaporate the toluene solvent after forming a mixture, and then use an ultrasonic oscillator to homogenize the mixture to obtain a modified polymethylsiloxane resin.
[0063] It should be noted that the modified filler includes nano-diamond particles and titanium dioxide nano-particles in a mass ratio of 3:12.
[0064] Wherein, the modified filler is prepared by the following method:
[0065] a. Nano-diamond particles with an average particle size of 20 nm and titanium dioxide nanoparticles were weighed and mixed to form a mixture A according to a mass ratio, ethanol was added to the mixture A, and the mixture was put into an ultrasonic dispersion device for a dispersion time of 0.5 h to obtain a mixed suspension, wherein the mass ratio of the mixture A to the ethanol was 1:40;
[0066] b. Slowly add the ionic liquid to the dispersed mixed suspension, wherein the ionic liquid is 1-butyl-3-methylimidazolium tetrafluoroborate solution, the ratio of the ionic liquid to the mixed solution B is 0.1:1, stir and mix at a stirring speed of 250 r / min, stir for 0.6 h, and then place at a temperature of 50°C for reaction for 3 h to obtain a mixed solution B;
[0067] c. Centrifuge the mixed solution B at 6000 r / min for 0.2 h;
[0068] d. The product after centrifugation of the mixed solution B was washed alternately with deionized water and an organic solvent for three times, and then transferred to a vacuum drying oven for vacuum drying at a temperature of 60°C and a drying time of 8 hours to obtain the desired modified filler.
[0069] A method for preparing a high-durability, low-friction optical coating comprises the following preparation steps:
[0070] S1. Weigh the raw materials modified polymethylsiloxane resin, nano boron nitride flakes, modified filler, fluorinated polyether, hyperbranched polysiloxane, bio-based solvent, and photoinitiator by weight for later use;
[0071] S2, adding the nano boron nitride flakes and the modified filler into the modified polymethylsiloxane resin, and performing ultrasonic dispersion to make them uniformly dispersed in the solvent;
[0072] S3, adding fluorinated polyether, hyperbranched polysiloxane, and bio-based solvent in sequence and stirring evenly;
[0073] S4. Add photoinitiator and stir again to obtain the desired high-durability and low-friction optical coating.
[0074] In order to verify the comprehensive performance of the high-durability, low-friction optical coatings prepared in Examples 1-3 of the present application, the applicant set up Comparative Examples 1-2, which are as follows:
[0075] Comparative Example 1:
[0076] The present invention provides a high-durability, low-friction optical coating formula, comprising the following raw materials in parts by weight: 60 parts of modified polymethylsiloxane resin, 15 parts of nano boron nitride flakes, 10 parts of modified fillers, 2 parts of fluorinated polyether, 1 part of hyperbranched polysiloxane, 5 parts of bio-based solvents, and 1 part of photoinitiator;
[0077] Specifically, the bio-based solvent is butyl acetate, and the photoinitiator is benzoin ethyl ether.
[0078] The modified polymethylsiloxane resin is polymethylsiloxane resin.
[0079] It should be noted that the modified filler includes nano-diamond particles and titanium dioxide nano-particles in a mass ratio of 3:5.
[0080] The modified filler is prepared by the following method:
[0081] a. Nano-diamond particles with an average particle size of 8 nm and titanium dioxide nanoparticles were weighed and mixed to form a mixture A according to a mass ratio, ethanol was added to the mixture A, and the mixture was put into an ultrasonic dispersion device for a dispersion time of 0.2 h to obtain a mixed suspension, wherein the mass ratio of the mixture A to the ethanol was 1:30;
[0082] b. Slowly add the ionic liquid to the dispersed mixed suspension, wherein the ionic liquid is 1-butyl-3-methylimidazolium tetrafluoroborate solution, the ratio of the ionic liquid to the mixed solution B is 0.1:1, stir and mix at a stirring speed of 200 r / min, stir for 0.5-1h, and then place at a temperature of 30°C for 1h to react to obtain a mixed solution B;
[0083] c. Centrifuge the mixed solution B at 4000 r / min for 0.1 h;
[0084] d. The product after centrifugation of the mixed solution B was washed alternately with deionized water and an organic solvent twice, and then transferred to a vacuum drying oven for vacuum drying at a temperature of 40°C and a drying time of 5 hours to obtain the desired modified filler.
[0085] A method for preparing a high-durability, low-friction optical coating comprises the following preparation steps:
[0086] S1. Weigh the raw materials modified polymethylsiloxane resin, nano boron nitride flakes, modified filler, fluorinated polyether, hyperbranched polysiloxane, bio-based solvent, and photoinitiator by weight for later use;
[0087] S2, adding the nano boron nitride flakes and the modified filler into the modified polymethylsiloxane resin, and performing ultrasonic dispersion to make them uniformly dispersed in the solvent;
[0088] S3, adding fluorinated polyether, hyperbranched polysiloxane, and bio-based solvent in sequence and stirring evenly;
[0089] S4. Add photoinitiator and stir again to obtain the desired high-durability and low-friction optical coating.
[0090] Comparative Example 2:
[0091] The present invention provides a high-durability, low-friction optical coating formula, comprising the following raw materials in parts by weight: 60 parts of modified polymethylsiloxane resin, 15 parts of nano boron nitride flakes, 10 parts of modified fillers, 2 parts of fluorinated polyether, 1 part of hyperbranched polysiloxane, 5 parts of bio-based solvents, and 1 part of photoinitiator;
[0092] Specifically, the bio-based solvent is butyl acetate, and the photoinitiator is benzoin ethyl ether.
[0093] The modified polymethylsiloxane resin is prepared by the following method:
[0094] Weigh polymethylsiloxane resin, graphene quantum dot solution, carbon nanotubes and toluene in a mass ratio of 20:2:2:70 for later use, mix the weighed polymethylsiloxane resin and toluene evenly to form a mixed solution with a concentration of 8%, add the weighed graphene quantum dot solution and carbon nanotubes to the mixed solution, stir and mix at room temperature for 4 hours at a stirring speed of 800 r / min, evaporate the toluene solvent after forming a mixture, and then use an ultrasonic oscillator to homogenize the mixture to obtain a modified polymethylsiloxane resin.
[0095] It should be noted that the modified fillers are nano-diamond particles and titanium dioxide nano-particles.
[0096] A method for preparing a high-durability, low-friction optical coating comprises the following preparation steps:
[0097] S1. Weigh the raw materials modified polymethylsiloxane resin, nano boron nitride flakes, modified filler, fluorinated polyether, hyperbranched polysiloxane, bio-based solvent, and photoinitiator by weight for later use;
[0098] S2, adding the nano boron nitride flakes and the modified filler into the modified polymethylsiloxane resin, and performing ultrasonic dispersion to make them uniformly dispersed in the solvent;
[0099] S3, adding fluorinated polyether, hyperbranched polysiloxane, and bio-based solvent in sequence and stirring evenly;
[0100] S4. Add photoinitiator and stir again to obtain the desired high-durability and low-friction optical coating.
[0101] Performance testing:
[0102] According to the test standards, the high-durability, low-friction optical coatings prepared in Examples 1-3 of the present application and Comparative Examples 1-2 were coated on glass surfaces to prepare test samples, which were placed in a test room at a temperature of 25°C and a relative humidity of 55% for 2 hours and then tested for their performance.
[0103] According to GB / T 9274-1988 "Determination of resistance of paints and varnishes to liquid media", the liquid medium resistance performance of the test specimens was tested. The specimen specifications were 40cmx40cm, the glass thickness was 0.5cm, and the coating thickness was 0.5mm.
[0104] According to GB / T 10006-1988 Determination of friction coefficient of plastic film and sheet, the friction coefficient of the test sample is determined. The specimen size is 40cmx40cm, the glass thickness is 0.5cm, and the coating thickness is 0.5mm.
[0105] The test results are shown in Table 1 below:
[0106]
[0107] It can be seen from the data shown in Table 1 above that the high-durability, low-friction optical coatings prepared in Examples 1-3 of the present application have high durability, a smooth surface, a low friction coefficient, and excellent comprehensive performance.
[0108] It can be seen from the data shown in Example 1 and Comparative Example 1 that Example 1 of the present application modifies the polymethylsiloxane resin by using a graphene quantum dot solution and carbon nanotubes, which can significantly improve the durability of the coating compared to directly adding the polymethylsiloxane resin, and at the same time, the volatility of volatile organic compounds is also reduced.
[0109] It can be seen from the data shown in Example 1 and Comparative Example 2 that Example 1 of the present application can further improve the durability and surface friction coefficient of the coating by treating the nano-diamond particles and titanium dioxide nanoparticles with ionic liquid.
[0110] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-durability, low-friction optical coating formulation, characterized in that: The invention comprises the following raw materials in parts by weight: 60-95 parts of modified polymethylsiloxane resin, 15-25 parts of nano boron nitride flakes, 10-25 parts of modified filler, 2-7 parts of fluorine-containing polyether, 1-5 parts of hyperbranched polysiloxane, 5-15 parts of bio-based solvent, and 1-3 parts of photoinitiator; The modified polymethylsiloxane resin is prepared by the following method: The polymethylsiloxane resin, graphene quantum dot solution, carbon nanotubes and toluene are weighed in a mass ratio of 20-30:2-3:2-3:70 for later use, the weighed polymethylsiloxane resin and toluene are evenly mixed to form a mixed solution with a concentration of 8%-25%, the weighed graphene quantum dot solution and carbon nanotubes are added to the mixed solution, and the mixture is stirred at room temperature for 4-7 hours at a stirring speed of 800-1000 r / min. After the mixture is formed, the toluene solvent is evaporated, and the mixture is homogenized by an ultrasonic oscillator to obtain a modified polymethylsiloxane resin.
2. A high-durability, low-friction optical coating formulation according to claim 1, characterized in that: The modified filler comprises nano-diamond particles and titanium dioxide nano-particles in a mass ratio of 3:5-15.
3. A high-durability, low-friction optical coating formulation according to claim 2, characterized in that: The modified filler is prepared by the following method: a. Weigh nanodiamond particles having an average particle size of 8-25 nm and titanium dioxide nanoparticles according to a mass ratio and mix them to form a mixture A. Add ethanol to the mixture A and put it into an ultrasonic dispersion device for a dispersion time of 0.2-0.6 h to obtain a mixed suspension. b. Slowly add the ionic liquid to the dispersed mixed suspension, stir and mix at a stirring speed of 200-300r / min, stir for 0.5-1h, and then react at a temperature of 30-70°C for 1-4h to obtain a mixed solution B; c. Centrifuge the mixed solution B at a speed of 4000-8000 r / min for 0.1-0.3 h; d. Wash the product after centrifugation of mixed solution B with deionized water and organic solvent alternately for 2-4 times, transfer it into a vacuum drying oven for vacuum drying, and obtain the desired modified filler.
4. A high-durability, low-friction optical coating formulation according to claim 3, characterized in that: The mass ratio of the mixture A to ethanol is 1:30-60, the ionic liquid is 1-butyl-3-methylimidazolium tetrafluoroborate solution, and the ratio of the ionic liquid to the mixed solution B is 0.1-0.2:
1.
5. A high-durability, low-friction optical coating formulation according to claim 3, characterized in that: The vacuum drying temperature is 40-70°C, and the drying time is 5-12 hours.
6. A high-durability, low-friction optical coating formulation according to claim 3, characterized in that: The bio-based solvent is butyl acetate, and the photoinitiator is benzoin ethyl ether.
7. A method for preparing a high-durability, low-friction optical coating according to any one of claims 1 to 6, characterized in that: The method comprises the following preparation steps: S1. Weigh the raw materials modified polymethylsiloxane resin, nano boron nitride flakes, modified filler, fluorinated polyether, hyperbranched polysiloxane, bio-based solvent, and photoinitiator by weight for later use; S2, adding the nano boron nitride flakes and the modified filler into the modified polymethylsiloxane resin, and performing ultrasonic dispersion to make them uniformly dispersed in the solvent; S3, adding fluorinated polyether, hyperbranched polysiloxane, and bio-based solvent in sequence and stirring evenly; S4. Add photoinitiator and stir again to obtain the desired high-durability and low-friction optical coating.
Citation Information
Patent Citations
Nanometer diamond-titanium hybrid modified high-thermal conductivity LED organosilicon packaging glue and preparation method thereof
CN106047275A
Residue-free restickable silica gel protective film and preparation method thereof
CN118109136A
Nanodiamond dispersion composition
JP2020132447A
Nanocomposites containing nanodiamond compounds and ionic liquids
KR1020110002618A
Property enhancing fillers for transparent coatings and transparent conductive films
US20160096967A1
